Investigation on the mechanism of coal desulfurization by ultrasonic with peroxyacetic acid. Issue 8 (18th April 2018) - Tang, Longfei; Fan, Huidong; Guo, Jifeng; Zeng, Weichen; Tao, Xiuxiang
ABSTRACT: This investigation reports the exploration of the mechanism for coal desulfurization utilizing ultrasonic (US) with peroxyacetic acid. Changes in surface and pore diameter for coal samples were determined before and after US treatment. To study its chemical effect, production regularities of hydroxyl radical under US field was analyzed by the iodine release method. Experimental results showed that the specific surface area, total pore volume and average pore size of treated samples were improved compared to untreated coal. In addition, the production rule of hydroxyl radical was consistent with that of desulfurization rate. XPS analysis results indicated that the removals of pyrite, mercaptan, and sulfur ether from coal were more than 60%, while thiophene, sulfoxide and sulfone were difficult to remove from coal. The further oxidation of sulfur-containing groups in coal was obtained due to the physical and chemical effects of the ultrasonic. These findings confirmed that the synergistic action of physical and chemical effects of the US played an important role in this desulfurization process, which could serve as a reference for further optimizing the coal desulfurization process.